EFEKTIFITAS PEMBUATAN KOMPOS MENGGUNAKAN AMPAS TAHU DENGAN MEDIA TAKAKURA - Muliyadi Muliyadi (Poltekkes Kemenkes Padang, 2021)
Ternate City is experiencing solid waste management problems, namely the problem of transporting waste, based on data from the environmental service in 2019, the availability of transportation infrastructure is only able to transport 100 tons of garbage per day. The purpose of this study was to determine the effectiveness of composting using tofu dregs with Takakura media. This research method is an experimental research type using a post-control design approach. The control variable was composting without Takakura media, while the treatment variable was composting with Takakura media. The aim is to compare the effectiveness of tofu dregs in composting. measurement results for 20 days for tofu dregs at a temperature of 32°C, a pH of 7.5 and a humidity of 60%. From the results of the study, it was found that the quality of the compost had met the standards based on SNI 2803:2010 and for the control, namely 31°C, pH 7.5 and humidity 60%. The conclusion is that the amount of compost produced for the two composts is different. Tofu pulp has a composting time of 20 days with the amount of compost as much as 5 0ns, meanwhile Control has a composting time of 20 days with the amount of compost as much as 2 ounces. It is recommended that further researchers use vegetables for composting using Takakura media because this material is very much found in households.